32.4k views
3 votes
Use the quadratic formula to solve the equation

Use the quadratic formula to solve the equation-example-1
User Samxiao
by
4.8k points

1 Answer

1 vote


\bf ~~~~~~~~~~~~\textit{quadratic formula}\\\\\stackrel{\stackrel{a}{\downarrow }}{1}x^2\stackrel{\stackrel{b}{\downarrow }}{-7}x\stackrel{\stackrel{c}{\downarrow }}{-6}=0\qquad \qquadx= \cfrac{ - b \pm \sqrt { b^2 -4 a c}}{2 a}\\\\\\x=\cfrac{ - (-7) \pm \sqrt { (-7)^2 -4(1)(-6)}}{2(1)}\implies x=\cfrac{7\pm√(49+24)}{2}\\\\\\x=\cfrac{7\pm√(73)}{2}\implies x=\begin{cases}\cfrac{7+√(73)}{2}\\[1.8em]\cfrac{7-√(73)}{2}\end{cases}

User Krasimir Stoev
by
5.5k points